Giving a Comment or Not? The Influence of Psychopathy Trait on Commenting on Social Media - Artana, Viona Muna; Nuzulia, Siti (Journal of Social and Industrial Psychology, 2023)
Personality usually also influences the preferences or interests that a person has. This interest thentriggers the desire in a person to behave well, both positive and negative behavior. Psychopathicpsychology itself is described as selfish, lacking feelings of empathy and remorse, impulsive,manipulative, more selfish, and tends to be antisocial. Research related to psychopathy andcommenting behavior on social media has not been carried out much. Therefore, this study aims tosee the effect of psychopathic personality on behavior to give comments on social media. Thisresearch is a quantitative research using quasi-experimental methods and one group post-testdesign. Quota sampling is used as a sampling technique. The research managed to collect 380respondents who were then divided into two different groups, namely the control group and theexperimental group. Both groups will be given the same treatment according to the existingprocedure. Data analysis was then performed using logistic regression analysis which was carriedout twice. While the results of the study show a significance value of 0.049 between so that it readsthat the hypothesis is accepted where secondary psychopathy has a negative effect on commentingbehavior in the experimental group with posting negative content.